Intravital imaging reveals synergistic effect of CAR T-cells and radiation therapy in a preclinical immunocompetent glioblastoma model. (1st January 2020) - Murty, Surya; Haile, Samuel T.; Beinat, Corinne; Aalipour, Amin; Alam, Israt S.; Murty, Tara; Shaffer, Travis M.; Patel, Chirag B.; Graves, Edward E.; Mackall, Crystal L.; Gambhir, Sanjiv S.
ABSTRACT: Recent advances in novel immune strategies, particularly chimeric antigen receptor (CAR)-bearing T-cells, have shown limited efficacy against glioblastoma (GBM) in clinical trials. We currently have an incomplete understanding of how these emerging therapies integrate with the current standard of care, specifically radiation therapy (RT). Additionally, there is an insufficient number of preclinical studies monitoring these therapies with high spatiotemporal resolution. To address these limitations, we report the first longitudinal fluorescence-based intravital microscopy imaging of CAR T-cells within an orthotopic GBM preclinical model to illustrate the necessity of RT for complete therapeutic response. Additionally, we detail the first usage of murine-derived CAR T-cells targeting the disialoganglioside GD2 in an immunocompetent tumor model. Cell culture assays demonstrated substantial GD2 CAR T-cell-mediated killing of murine GBM cell lines SB28 and GL26 induced to overexpress GD2. Complete antitumor response in advanced syngeneic orthotopic models of GBM was achieved only when a single intravenous dose of GD2 CAR T-cells was following either sub-lethal whole-body irradiation or focal RT. Intravital microscopy imaging successfully visualized CAR T-cell homing and T-cell mediated apoptosis of tumor cells in real-time within the tumor stroma. Findings indicate that RT allows for rapid CAR T-cell extravasation from the vasculature and expansion within the tumor microenvironment, leading to a more robust and lasting immunologic response. These exciting results highlight potential opportunities to improve intravenous adoptive T-cell administration in the treatment of GBM through concurrent RT. Additionally, they emphasize the need for advancements in immunotherapeutic homing to and extravasation through the tumor microenvironment.